2021
DOI: 10.3390/coatings11111289
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Treatment on the Microstructure and Phase Composition of Plasma Sprayed Al2O3 and Al2O3-TiO2 Coatings for Applications in Biomass Firing Plants

Abstract: This study presents the thermal and chemical resistance of plasma-sprayed Al2O3 and Al2O3 doped with 13 wt.% of TiO2 coatings and their suitability for the fire grate of straw pellet furnaces. Coatings were deposited on steel substrates using direct current atmospheric pressure plasma spraying. The surface structure, elemental, and phase composition of formed coatings were analyzed before and after the thermal treatment, imitating natural application conditions. For the experiment, the annealing temperature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The phase transformation of amorphous Al 2 O 3 to crystalline α-Al 2 O 3 often requires heat treatment at elevated temperatures [57]. In one study, anodic aluminum oxide (AAO) films were formed in a 15% H 2 SO 4 solution by the anodizing method, and the prepared AAO films were heat-treated in the temperature range of 25 Tian et al [33] anodized Al alloys of 99.999% purity in an oxalic acid electrolyte using the two-step anodizing method. Before anodizing, the samples were annealed at 500 • C for 2 h in a nitrogen environment.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase transformation of amorphous Al 2 O 3 to crystalline α-Al 2 O 3 often requires heat treatment at elevated temperatures [57]. In one study, anodic aluminum oxide (AAO) films were formed in a 15% H 2 SO 4 solution by the anodizing method, and the prepared AAO films were heat-treated in the temperature range of 25 Tian et al [33] anodized Al alloys of 99.999% purity in an oxalic acid electrolyte using the two-step anodizing method. Before anodizing, the samples were annealed at 500 • C for 2 h in a nitrogen environment.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that the spraying of Al 2 O 3 using standard thermally sprayed techniques usually reduces the content of α-Al 2 O 3 , due to its transformation to the γ-Al 2 O 3 phase [49,50]. On the other hand, the phase transformation of α-Al 2 O 3 to γ-Al 2 O 3 may be significantly reduced by 8.7% using plasma-sprayed Al 2 O 3 coatings doped with 13 wt% TiO 2 [25]. Michalak et al [26] demonstrated that high velocity oxygen fuel spraying and plasma spraying using Al 2 O 3 aqueous suspensions resulted in αphase rich Al 2 O 3 coatings of up to 47 vol% and 62 vol%, respectively.…”
Section: Thermal Sprayingmentioning
confidence: 99%
“…Using a direct-current (DC) plasma torch developed at the Lithuanian Energy Institute (Kaunas, Lithuania), Al 2 O 3 coatings were applied to steel (P265GH) substrate at atmospheric pressure [26,27].…”
Section: Methodsmentioning
confidence: 99%